Ước lượng cầu sản phẩm cá cho trường hợp Việt Nam: Sự thay đổi trong kiểu hình tiêu dùng qua thời gian - Phạm Đình, Long; Huỳnh Công, Toại (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
The paper indicates the analysis results of Vietnamese household’s consumption demand for fish product by using LA/AIDS model. It not only assesses the impact factors on the patterns of fish product consumption, but reflects the flexibility in consumption tendency during the period of time. Using the cross-sectional data drawn from VHLSS 2010, VHLSS 2012 and VHLSS 2014, the estimates are made by applying SUR method through Heckman’s two-step correction. In the study, we place tight constraints on the uniformity and symmetry in an estimated model. The results show that income elasticity of demand for fish product increases though it has become a basic and common commodity. The fish consumption in urban areas seems to have greater sensitivity to price fluctuations than the one in rural areas due to some differences in the general price level. The changes in price have weaker impacts on the low-income households than ones in the highest income group.